High precision material removal of copper surface by jet electrochemical machining. (January 2020) - Feng, Yiming; Yan, Ying; Zhou, Ping; Guo, Dongming
Abstract: High-precision machining technology has attracted increasing attention with the rapid development of modern industry. Jet electrochemical machining is a promising method for forming complex 3D shape surface by controlling the path and dwelling time of electrode nozzle moving over workpiece surface. The machining accuracy mainly relies on the stability of the material removal rate and the smoothness of the machined surface. In this paper, a new jet electrochemical machining method, which is based on a newly developed acid electrolyte, is proposed to improve its machining performance. The effects of voltage, interelectrode gap, electrolyte temperature and flow rate are discussed in this work. Stable machining can be achieved by selecting the optimum process parameters, and the surface roughness (Ra) can be reduced to 14.8 nm. Moreover, the obtained material removal rate distribution agrees well with the Gaussian function, which is recognized to have high capability to form complex 3D surface through controlling the movement of the tools.